Polymer Binders of Ceramic Nanoparticles for Precision Casting of Nickel-Based Superalloys - Wiśniewski, Paweł (Nanomaterials (Basel, Switzerland), 2021)
This study presents the general characteristics of binders used in precision casting of Nickel-based superalloys. Three groups of binders were described: resins, organic compounds, and materials containing nanoparticles in alcohol or aqueous systems. This study also includes literature reports on materials commonly used and those recently replaced by water-soluble binders, i.e., ethyl silicate (ES) and hydrolysed ethyl silicate (HES). The appearance of new and interesting solutions containing nano-alumina is described, as well as other solutions at the initial stage of scientific research, such as those containing biopolymers, biodegradable polycaprolactone (PCL), or modified starch. Special attention is paid to four binders containing nano-SiO2 intended for the first layers (Ludox AM, Ludox SK) and structural layers (EHT, Remasol) of shell moulds. Their morphology, viscosity, density, reactions, and electrokinetic potential were investigated. The binders were characterized by a high solid-phase content (>28%), viscosity, and density close to that of water (1–2 mPa·s) and good electrokinetic stability. The nanoparticles contained in the binders were approximately spherically shaped with an average particle size of 16–25 nm.